Ms.Liang is building a deck that is 2 2/9 yards long and 3 2/5 yards wide what is the area of her deck.

Answers

Answer 1
Answer:

Answer:

length = 20/9 yards

breadth = 17/5 yards

area = length x breadth

= 20/9 x 17/5 = 7 5/9 sq. yards


Related Questions

3 - 3 × 6 + 2 = what
The original price p of an item less a discount of 40%
Help ASAP 27 points.I'll mark you brainliest of you answer correctly.​
The ordered pairs below represent a linear relation between x and y.(-3,1), (-2,3), (-1,5), (0,7), (1,9), (2,11) Which of the following is a correct statement about this relation? A. The slope of the line represented by this table is -2 and the y-intercept is -4. B. The slope of the line represented by this table is 2 and the y-intercept is 7. C. The slope of the line represented by this table is 2 and the y-intercept is -4. D. The slope of the line represented by this table is -2 and the y-intercept is 7.
The altitude of an equilateral triangle is 18 inches. Find the length of a side

Which of the following best explains why tan 5pi/6 does not equal to tan 5pi/3?A. The angles do not have the same reference angle.
B. Tangent is positive in the second quadrant and negative in the fourth quadrant.
C. Tangent is negative in the second quadrant and positive in the fourth quadrant.
D. The angles do not have the same reference angle or the same sign.

Answers

Option A. The angles do not have the same reference angle.

Explanation:

1) Angle 5π / 3 radians:

  • Convert radians to degrees: 5π/3 × 180° / π = 300°
  • 300° is in the fourth quadrant
  • The reference angle for angles in the fourth quadrant is 360° - angle ⇒ 360° - 300° = 60°.
  • ∴ The reference angle for this angle is 60°.

2) Angle 5π / 6 radians:

  • Convert radians to degrees: 5π/6 × 180° / π = 150°
  • 150° is in the second quadrant
  • The reference angle for angles in the second quadrant is 180° - angle ⇒ 180° - 150° = 30°.
  • ∴ The reference angle for this angle is 30°.

3) Conclusion:

  • Since the reference angles are different, the tangent ratios have different values.
  • tan (5π/3) = - tan(60°) = - √3
  • tan (5π/6) = - tan(30°) = - (√3)/3

Note that the tangent is negative in both second and fourth quadrants.

Answer:

The correct option is A.

Step-by-step explanation:

The first expression is,

\tan ((5\pi)/(6))

\tan ((6\pi-\pi)/(6))

\tan (\pi-(\pi)/(6))

The reference angle is (\pi)/(6) . In second quadrant the sign of tangent is negative.

-\tan ((\pi)/(6))

-(1)/(√(3))

The second expression is,

\tan ((5\pi)/(3))

\tan ((6\pi-\pi)/(3))

\tan (2\pi-(\pi)/(3))

The reference angle is (\pi)/(3) . In fourth quadrant the sign of tangent is negative.

-\tan ((\pi)/(3))

-√(3)

Since the sign are same but the reference angle is are different, therefore the correct option is A.

How many milliliters are in 30 Liters?
300
3,000
30,000
300,000

Answers

In this question, there is nothing complicated. only thing that needs to be done is to convert 30 liters into milliliters. For this purpose it is important to know the number of milliliters in 1 liter. then the problem becomes very easy to solve.
1 liter = 1000 milliliters
then
30 liters = (1000/1) * 30 milliliters
             = 1000 * 30 milliliters
             = 30000 milliliters
So from the above deduction we can conclude that the third option of 30000 is the correct option,. i hope there is nothing uncomplicated in the procedure for you to understand.

my guy u could've just said 30000


Melinda bought 6 bowls for $13.20. what was the unit rate in dollars

Answers

To find the unit rate we will divide the amount of dollars ($13.20) by the amount of bowls (6). Then we will check our work. lets do it:-

13.20 ÷ 6 = 2.20
$2.20 per bowl

CHECK OUR WORK:-

2.20 × 6 = 13.20
we were RIGHT!!

So, the unit rate in dollars for, Melinda bought 6 bowls for $13.20  is, $2.20 per bowl.

Hope I helped ya!! xD
Just put  this ,      13.20/6 which is 2.20 so thats 2.20$ a bowl.
also you could , 2.20*6=13.20 , thats still 13.20 (2.20)

all together this means the unit rate in dollar is 2.20 for bowl , per bowl. for Melinda because she bought them for 13.20


i hope this helps.


Kevin, Conner, and John each walk several miles per day as part of a fitness program. Kevin walks 3 miles less than Conner, and John walks 2 miles more than Conner does. Over 3 days the difference between the number John and Kevin walk is equal to one half the number of miles that Conner walks. How many miles does each person walk each day?

Answers

Answer:

The distance Conner walks each day is 10 miles

The distance Kevin walks each day is 7 miles

The distance John walks each day is 12 miles

Step-by-step explanation:

The question is a word problem

Let the number of miles Conner walks per day = x

The given inforf the totmation in the question are;

The distance Kevin walks per day = x - 3 miles

The distance John walks per day = x + 2 miles

In three days, the difference between the total distance John walks and the total distance Kevin walks is equal to half the total distance Conner walks

The number of miles each person walks per day is found as follows;

3×(x + 2) - 3×(x - 3) = 3·x/2

3·x + 6 - 3·x - (-9) = 3·x/2

3·x + 6 - 3·x + 9 = 3·x/2

3·x - 3·x + 6  + 9 = 3·x/2

0 + 6  + 9 = 3·x/2

15 = 3·x/2

x = 15×2/3 = 10 miles

x = 10 miles

Therefore, the distance Conner walks each day = 10 miles

The distance Kevin walks per day = (x - 3) miles = (10 - 3) miles = 7 miles

The distance Kevin walks per day = 7 miles

The distance John walks per day = (x + 2) miles = (10 + 2) miles = 12 miles

The distance John walks per day = 12 miles.

Simplify (-1)(1)(-1)(1)(-1)

Answers

Answer: -1

Explanation:

Answer:

-1^(3)1^(2) or -1

Step-by-step explanation:

-1*1=-1*-1=1

1*1=1*-1=-1

Hope This helps

(ps i know the des is confusing. sry)

How do you solve the following exponential equation by expressing each power of the same base and then equating the exponents?6^x-3/4= square rot of 6

Answers

Start by switching everything into exponent form: 6^(x-3/4)=6^(1/2). In this equation, we're trying to find the value of x that will make each side equal. Because the base (6) is the same on either side of the equal sign, all we need to worry about is the exponents, because this equation can only be true if the exponents are the same (i.e. 6^(1/2)=6^(1/2)). Thus, you can actually ignore the 6's entirely and only focus on the exponents: x-3/4=1/2. Then, this has just become a simple algebraic expression. x-3/4+3/4=1/2+3/4. x=1/2(2/2)+3/4. x=2/4+3/4. x=5/4
6^{x-\tfrac{3}{4}}=√(6)\n6^{x-\tfrac{3}{4}}=6^{\tfrac{1}{2}}\nx-(3)/(4)=(1)/(2)\nx=(1)/(2)+(3)/(4)\nx=(2)/(4)+(3)/(4)\nx=(5)/(4)